3D gravity and magnetic inversion reveal geothermal structure dominated by radioactive heat production of granites in the Weihe basin - Feng, Xuliang; Ma, Jiayue; Guo, Ruikun; Zhang, Jin’ai; Yang, Liu (Tectonophysics, 2024)
The Weihe basin possesses abundant in medium-low temperature geothermal resources. However, the primary source of heat in the basin, whether it stems from the mantle or crust, remains a subject of debate. In this study, we employ three-dimensional inversion of gravity and magnetic anomalies to ascertain the basement depth, Moho depth, Curie point depth, and spatial distribution of magnetic bodies within the Weihe basin. Our findings reveal that there is no correlation between heat flow and mantle uplift and the uplift area of the Moho does not coincide with the depocenter of the basin. These results suggest that the mantle heat brought by lithosphere thinning and stretching is not the predominant heat source in the Weihe basin. Furthermore, we observe a significant discrepancy in Curie point depth between the northern and southern sides of the Weihe fault within this region, indicating its role as a suture zone connecting two structural units throughout geological history. Through three-dimensional susceptibility inversion analysis, we identify a widespread distribution of magnetic bodies (primarily Yanshanian granites) beneath sediments within the Weihe basin which are connected to the granites located in the North Qinling area. This suggests that the granites formation within the Weihe basin may have occurred concurrently with the magmatic activity in the North Qinling area. Since Cenozoic timescale, northeastward compression exerted by the Tibet Plateau has resulted in passive strong fault depression within the Weihe basin while burying the previously intruded granites under thick sedimentary layers on a massive scale. These buried granites release heat through radioactive decay processes making them an essential heat source for the medium-low temperature geothermal fields. •Thermal structure of the Weihe basin is revealed by 3D gravity and magnetic inversion.•Mantle heat caused by lithosphere thinning is not the dominant heat source.•The Weihe basin is passively extensional rifted as Tibetan plateau moves to the northeast.•The Weihe basin has been devoid of magmatic activity since its formation.•The dominated heat source of the Weihe basin is radioactive heat production of granites.